Food safety knowledge, needed and trusted information of pork consumers in different retail types in Northern Vietnam - Trang Thi-Huyen Le; Langley, S.J.; Dunham, J.G.; Sinh Dang-Xuan; Unger, Fred; Hai Hoang Tuan Ngo; Luong Nguyen-Thanh; Hung Nguyen-Viet; Toribio, Jenny-Ann (Frontiers Media, 2022)
Introduction: Food safety is an important public health concern globally. Risk communication is one of crucial element to manage food safety. While current food safety studies have focused on contamination of hazards or risk factors, limited research exists on consumer concerns, knowledge and perception about the actual risk food poses to their health. This study aimed to assess and compare the knowledge and perceptions regarding food safety, and the information needed and trusted by pork consumers in Northern Vietnam.